2017
DOI: 10.1186/s12902-017-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of adrenal crisis in adult population with and without predisposing chronic adrenal insufficiency: a retrospective cohort study

Abstract: BackgroundAdrenal crisis (AC) occurs in various clinical conditions but previous epidemiological studies in AC are limited to chronic adrenal insufficiency (AI) and sepsis. The aim of this study was to investigate characteristics of AC patients, including predisposing diseases and to describe candidate risk factors for AC such as comorbidities and glucocorticoid (GC) therapy.MethodsWe conducted a retrospective cohort study using a claims database on 7.4 million patients from 145 acute care hospitals between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
13
1
2
Order By: Relevance
“…Such misclassification in older age groups would distort the observed relationship between older age and AC risk and may encourage a mistaken belief that AI/AC is less important in older people. The higher prevalence of AI in older relative to younger people also means that comparisons of AC rates between groups may be further confounded by demographic differences, due to the relationship between age and difficulties with AC diagnosis 9,11‐13 . Improved AC identification in older patients would not only be of great benefit to research and surveillance of AI/AC; it should also improve the acute and longer term management of individual patients, as the circumstances of each AC should be reviewed with the patient following treatment to identify precipitants and develop strategies that could be used to prevent another episode 2,4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Such misclassification in older age groups would distort the observed relationship between older age and AC risk and may encourage a mistaken belief that AI/AC is less important in older people. The higher prevalence of AI in older relative to younger people also means that comparisons of AC rates between groups may be further confounded by demographic differences, due to the relationship between age and difficulties with AC diagnosis 9,11‐13 . Improved AC identification in older patients would not only be of great benefit to research and surveillance of AI/AC; it should also improve the acute and longer term management of individual patients, as the circumstances of each AC should be reviewed with the patient following treatment to identify precipitants and develop strategies that could be used to prevent another episode 2,4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Another retrospective cohort study showed that 36 adrenal crises (7.1% of all cases) occurred within 30 days of discontinuation of glucocorticoids. 152 Adrenal crises have also been reported in patients tapering down inhaled glucocorticoids or switching between different glucocorticoid preparations. 153 Risks associated with inhaled glucocorticoid therapy Cases of symptomatic GI-AI and iatrogenic Cushing's syndrome have been linked to inhaled glucocorticoids.…”
Section: Clinical Relevance Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
“…Several cases of adrenal crisis and hospital admission for GI-AI have been described, including a few deaths 1435147148149150. Of note, many patients presenting with adrenal crisis were treated with inhaled glucocorticoids only (mostly high dose fluticasone propionate), emphasizing the potential risks associated with their systemic absorption 1455150151152153. Symptomatic GI-AI and adrenal crises have also been described in patients exposed to oral glucocorticoids for less than two months, as well as in patients receiving topical, intra-articular, epidural, and rectal glucocorticoids 148587150154155156157158.…”
Section: Clinical Relevance Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
“…The German observational study described above [28] found that a higher proportion of adrenal crisis episodes were caused by febrile infections than by infections involving vomiting. Studies of patients in the Netherlands, Japan and Australia have all found higher rates of adrenal crisis requiring hospital treatment for influenza and other infections [43][44][45][46]. Thus, vomiting and diarrhoea could arguably be over-represented as a trigger factor among the UK support group members studied here, compared to wider patient samples.…”
Section: Discussionmentioning
confidence: 74%